Thriving Through Turbulence: How Young Entrepreneurs Leverage Marketing Strategies to Navigate Crises and Digital Disruption - Saleh, Yusuf; Nurhilalia, N. (Manunggal Halim Jaya, 2025)
An era marked by global crises and accelerating digital transformation, young entrepreneurs face mounting challenges in maintaining business continuity. This study explores how youth-led ventures utilize digital marketing strategies to adapt, survive, and grow in the face of disruption. Drawing on theories of entrepreneurial resilience, digital innovation, and strategic marketing, the research employs a quantitative descriptive design to examine the behaviors and preferences of young entrepreneurs in turbulent environments. Data were collected through a structured survey targeting founders aged 18 to 35 across diverse industries. The analysis reveals that the most frequently adopted strategies include real-time social media engagement, influencer partnerships, A/B testing, content personalization, and the use of analytics dashboards. These strategies are positively associated with customer retention, brand visibility, and perceived business resilience. Additionally, the study finds that younger entrepreneurs tend to benefit more from platform-native features and interactive digital tools compared to their older counterparts. The findings highlight the critical role of adaptability, data-driven decision-making, and emotional branding in navigating crises. While digital marketing is not a one-size-fits-all solution, its strategic application significantly contributes to the sustainability and competitive positioning of youth-led businesses. This study contributes to the growing body of literature on digital entrepreneurship and offers actionable insights for policy makers, educators, and business development programs seeking to support resilient entrepreneurial ecosystems in uncertain times.